PENYISIHAN ION LOGAM MERKURI (Hg2+) MENGGUNAKAN ADSORBEN BERBAHAN BAKU LIMBAH PERTANIAN DAN GULMA TANAMAN - Miftahurrahmah, Suhendrayatna, Muhammad Zaki (Jurnal Teknik Kimia USU, 2017)
This research was conducted to prepare adsorbents from agricultural and weeds waste biomass to remove Hg2+ metal ions from water phase. Water hyacinth biomass (agricultural waste) and rice husk (weed) was cleaned, dried in an oven dryer, and carbonized in a furnace at 500oC for 2 hours. Then, dried carbon was milled to get 100 mesh of size and was followed by activation using 0.5 N NaOH. The adsorption process was conducted by mix 1 gram of activated adsorbent on a 100 ml water containing 3 ppm Hg2+ metal ions at 100 rpm, pH 5, and 30oC. Hg2+ concentration in water phase were analyzed using AAS, Shimadzu AA-6300 for a specified time within a period of 20-100 minutes. This study shows that at the beginning process of adsorption, adsorbent from rice husk has ability to decrease 69.91% concentration of Hg2+ for 20 minutes, while adsorbent from water hyacinth reaches to 94.26%. The characterization results of FTIR spectra and SEM shows that adsorbent from water hyacinth was able to absorb more Hg2+ metal ions in a short time because it has a functional group that was able to bind heavy metals, and also has a random surface structure, compared with the adsorbent from rice husks that has less functional groups with uniform morphology structure